2020
DOI: 10.5796/electrochemistry.20-00021
|View full text |Cite
|
Sign up to set email alerts
|

A Human Pathogen <i>Capnocytophaga Ochracea</i> Exhibits Current Producing Capability

Abstract: Microbial extracellular electron transfer (EET) in diverse environments has gained increasing attention. However, the EET capability of oral pathogens and associated mechanisms has been scarcely studied. Here, our results suggest that the Capnocytophaga ochracea, an etiological human pathogen showed current production and demonstrated a rate enhancement of electron transport at a high cell-density. C. ochracea produced~10-fold more current at an OD 600 of 0.5 associated with twice a higher glucose consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Microbes that exchange electrons with donors and acceptors in their external environment under anaerobic conditions have important roles in the biogeochemical cycling of carbon, metals, and nutrients; the anaerobic conversion of organic wastes to methane; a number of proposed bioelectrochemical technologies; and the corrosion of metals. āˆ’ The known diversity of microbes capable of extracellular electron transfer continues to rapidly expand both as new isolates are recovered in culture (for recent examples, see refs ā€“ ) and as microbes previously isolated for other physiological capabilities are discovered to have the capability for extracellular electron transfer. āˆ’ Remarkably, even though it has been known for some time that the capacity for extracellular electron transfer is widespread throughout the microbial world, , many isolates are not routinely tested for this physiological capability.…”
Section: Introductionmentioning
confidence: 99%
“…Microbes that exchange electrons with donors and acceptors in their external environment under anaerobic conditions have important roles in the biogeochemical cycling of carbon, metals, and nutrients; the anaerobic conversion of organic wastes to methane; a number of proposed bioelectrochemical technologies; and the corrosion of metals. āˆ’ The known diversity of microbes capable of extracellular electron transfer continues to rapidly expand both as new isolates are recovered in culture (for recent examples, see refs ā€“ ) and as microbes previously isolated for other physiological capabilities are discovered to have the capability for extracellular electron transfer. āˆ’ Remarkably, even though it has been known for some time that the capacity for extracellular electron transfer is widespread throughout the microbial world, , many isolates are not routinely tested for this physiological capability.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial membranes play a key role in mediating cellular and extracellular activities between living cells and their environment and in helping bacteria adapt to new conditions for their survival. It has been recently discovered that C. ochracea possesses unique properties of extracellular electron transfer (EET) to solid surfaces via their outer membrane (Zhang et al, 2020). OMVs are usually enriched with important OM characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…However, for other human electrogenic pathogens such as Klebsiella pneumoniae, Enterococcus avium, Enterococcus faecalis, Capnocytophaga ochracea, A. actinomycetemcomitans, and P. gingivalis, current production/mineral reduction mechanisms are unclear because they do not have any genes that encode conclusive or well-characterized EET pathways (Naradasu et al, 2018(Naradasu et al, , 2020bPankratova et al, 2018;Zhang et al, 2020b). Recent studies have identified redox species at the cell surface and membrane in S. mutans (Naradasu et al, 2020a), C. matruchotii (Naradasu et al, 2020c), A. actinomycetemcomitans, and P. gingivalis (Naradasu et al, 2020b) by DAB staining and electrochemical analysis suggesting that EET might be involved in current production.…”
Section: Reviewmentioning
confidence: 99%
“…This oxygen gradient suggests the possibility of long-range EET in oral biofilms, where anaerobes deep in the biofilm can transfer electrons to the aerobic space for reduction by oxygen (as the final electron acceptor). The main members of the oral biofilm, Streptococcus mutans, Capnocytophaga ochracea, Corynebacterium matruchotii, Aggregatibacter actinomycetemcomitans, and Porphyromonas gingivalis (Naradasu et al, 2020a(Naradasu et al, , 2020b(Naradasu et al, , 2020cZhang et al, 2020b), can produce electric current with cell-surface redox species. Given cell-surface redox regents can mediate lateral electron transport across microbial aggregation (Okamoto et al, 2012;Chong et al, 2019), it is possible that these electrogenic pathogens can exchange electron in the polymicrobial biofilm.…”
Section: The Eco-physiological Role Of Eet In Electrogenic Pathogens mentioning
confidence: 99%